Description of the male of Phoebe ornator (Tippmann, 1960) (Coleoptera: Cerambycidae: Lamiinae: Hemilophini), analysis of the species biogeography, and first observation of chromatic gender dimorphism in Hemilophini - Perger, Robert; Santos-Silva, Antonio; Guerra, Fernando (Zootaxa, 2017)
The male of Phoebe ornator (Tippmann, 1960) is described. Chromatic gender dimorphism is also reported for the first time in the Hemilophini. In addition, new records are presented for P. ornator for the Brazilian states of Amazonas, Mato Grosso, Rondônia and São Paulo, and the Bolivian department of La Paz. The biogeography of P. ornator is analyzed.